1974
DOI: 10.1126/science.185.4153.784
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Analysis of Chromosomal Abnormalities: Detection of a Deletion in Aniridia/ Wilms' Tumor Syndrome

Abstract: A chromosome translocation, t(8p + ; 11q -), in a patient with aniridia and Wilms' tumor, appeared balanced by standard techniques, including trypsin banding. Computer analysis of optical microscope scanning profiles of chromosome pairs 8 and 11 revealed an interstitial deletion of the short arm of 8. Computer analysis coupled to the new banding techniques provides greater resolution for the detection of subtle chromosomal variations not recognized by banding methods alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Figure 3 shows high-resolution idiograms of the normal chromosomes 8 and 11 with arrows pointing to the presumed break points. The composition of the rearranged chromosomes is expressed in Paris Con ference (1971) nomenclature as follows: der(8) = 8qter--8p21.2: : 11 q 14.4-»-1 lqter (this interpretation is consistent with the computer profiles of Ladda et al (1974) showing that part of 8p is missing from this derivative chromosome); d er(ll) -8pter…”
Section: Cytogenetic Studiessupporting
confidence: 60%
“…Figure 3 shows high-resolution idiograms of the normal chromosomes 8 and 11 with arrows pointing to the presumed break points. The composition of the rearranged chromosomes is expressed in Paris Con ference (1971) nomenclature as follows: der(8) = 8qter--8p21.2: : 11 q 14.4-»-1 lqter (this interpretation is consistent with the computer profiles of Ladda et al (1974) showing that part of 8p is missing from this derivative chromosome); d er(ll) -8pter…”
Section: Cytogenetic Studiessupporting
confidence: 60%
“…Fraumeni and Glass [3] examined 5 cases and found normal karyo types. 1 case described by Ladda et al [6] was reported to have an interstitial deletion of the short arm of chromosome 8. We have recently seen a case of aniridia, cataract and gonadoblastoma, but no Wilms' tumour, in a child with an interstitial deletion of chro mosome 11.…”
mentioning
confidence: 99%
“…The association of Wilms' tumor in five of 15 cases of sporadic aniridia was reported by Fraumeni and Glass (1968). Ladda et al (1974) recently, reported the partial deletion of chromosome 8 in this syndrome. The association of sporadic aniridia-Wilms' tumor and deletion in the short arm of chromosome 8 has important implications for the genetic causes of childhood cancer and the two-mutation model of tumorigenesis (Kundson and Strong, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, chromosomal aberation in cases of aniridia-Wilms' tumor syndrome have been detected recently- (Ladda et al, 1974;Andersen et al, 1978). Thus, this syndrome has attracted interest from the teratogenic and onchogenic points of view.…”
Section: Introductionmentioning
confidence: 99%